Experimental study on fresh, mechanical properties and embodied carbon of concrete blended with sugarcane bagasse ash, metakaolin, and millet husk ash as ternary cementitious material - Bheel, N. (Springer Science and Business Media Deutschland GmbH, 2022)
In recent years, the research direction is shifted toward introducing new supplementary cementitious materials (SCM) in lieu of in place of Portland cement (PC) in concrete as its production emits a lot of toxic gases in the atmosphere which causes environmental pollution and greenhouse gases. SCM such as sugarcane bagasse ash (SCBA), metakaolin (MK), and millet husk ash (MHA) are available in abundant quantities and considered as waste products. The primary aim of this experimental study is to investigate the effect of SCBA, MK, and MHA on the fresh and mechanical properties of concrete mixed which contributes to sustainable development. A total of 228 concrete specimens were prepared with targeted strength of 25MPa at 0.52 water-cement ratio and cured at 28 days. It is found that the compressive strength and split tensile strength were enhanced by 17 and 14.28, respectively, at SCBA4MK4MHA4 (88 PC, 4 SCBA, 4 MK, and 4 MHA) as ternary cementitious material (TCM) in concrete after 28 days. Moreover, the permeability and density of concrete are found to be reduced when SCBA, MK, and MHA are used separately and combined as TCM increases in concrete at 28 days, respectively. The results showed that the workability of the fresh concrete was decreased with the increase of the percentage of SCBA, MK, and MHA separately and together as TCM in concrete. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.